SEGMENTASI PASAR TERHADAP PENINGKATAN PENJUALAN KEJU MOZZARELLA DI KOTA MALANG - Nugroho, Anung Prasetyo; Suroto, Karunia Setyowati (Universitas Tribhuwana Tunggadewi, 2023)
This research aimed to determine whether the advertising division had a partial and synchronous impact on the expansion of deal execution at CV. Narendra Food Company. The type of research used is quantitative, namely a research approach testing speculation through numerical estimation of factors and analysis of information using measurable methods, as well as referring to theory testing. This inspection uses a purposive testing strategy. This examination totaled 105 respondents with the composition of customers who purchased mozzarella cheese. The result showed positive and noteworthy influence from the showcase division, especially the geographic showcase division, statistical showcase division, and psychographic market segmentation partially or independently on the expansion of transaction execution at CV. Narendra Food Company.